0D boron carbon nitride quantum dots decorated 2D Bi4O5I2 as 0D/2D efficient visible-light-driven photocatalysts for tetracyclines photodegradation. (February 2022) - Xu, Kailin; Zhang, Qiuya; Wang, Chuqiao; Xu, Jinmei; Bu, Yiming; Liang, Bin; Liu, Yushuai; Wang, Liping
Abstract: A series of 0D boron carbon nitride quantum dots (BCNQDs) modified 2D Bi4 O5 I2 (0D/2D Bi4 O5 I2 /BCNQDs) composites were synthesized and applied to photodegradation of tetracyclines (TCs), including tetracycline (TC) and oxytetracycline (OTC). The Bi4 O5 I2 /BCNQDs (1) (1 mL BCNQDs) composite exhibits the highest photocatalytic performance for TCs degradation. The degradation rate constants of TC and OTC by the optimal sample were 4.95 and 2.17 times that of Bi4 O5 I2, respectively. This can be attributed to the fact that the narrow bandgap Bi4 O5 I2 is the electron acceptor, and the oxygen-containing functional group with the negative charge on BCNQDs can promote the formation of photoexcited holes, which makes the effective separation of photoexcited carriers easier. Furthermore, the active substance (h + and ·O2 − ) is the major active substance for TCs photodegradation. On this basis, the possible photocatalytic reaction mechanism of Bi4 O5 I2 /BCNQDs (1) composite is proposed. This study provides a new idea for 0D/2D interface engineering of BCNQDs heterojunction. Graphical abstract: Image 1 Highlights: The novel 0D/2D Bi4 O5 I2 /BCNQDs photocatalysts were successfully prepared for the first time. ·O2 − and h + are responsible for TCs photodegradation by Bi4 O5 I2 /BCNQDs (1). The mechanism of TCs photodegradation was well discussed. The intermediates toxicity of TCs degradation by Bi4 O5 I2 /BCNQDs (1) are evaluated by QSAR method.